Consumption of mate Ilex paraguariensis: a folk beverage with antioxidant power against myocardial ischemic injury - Eduarda Santa-Helena; Micheli Castro; Francine Novack Victoria; Jonathan Souza Rodrigues; Carla Amorim Neves Gonçalves (Acta Scientiarum. Health Sciences, 2022)
The effects of the aqueous extract of Ilex paraguariensis (Ip) and the flavonoid quercetin were tested during the induction of in vivo myocardial ischemia/ reperfusion in Rattus norvegicus. The antioxidant power of the extract and quercetin were chemically determined. The experimental groups were: control, ischemia/reperfusion induction, Ip oral treatment, Ip oral treatment and ischemia /reperfusion, quercetin oral treatment, and quercetin oral treatment and ischemia/reperfusion. Rats were anesthetized with sodium thiopental and xylazine via intraperitoneal injection and subsequently underwent 15 minutes of ischemia followed by 15 minutes of reperfusion. Ischemia was promoted by tying the left anterior descending coronary artery. Areas of risk and infarction were stained by intravenous Evans blue and triphenyl tetrazolium chloride. Reactive oxygen species (ROS), antioxidant capacity against peroxyl radicals, and lipid peroxidation of the myocardium were quantified. A significant reduction in areas of risk and infarction was detected in the ischemic myocardium treated with Ip and quercetin; ROS generation and lipid peroxidation were significantly reduced, and the antioxidant capacity was elevated. Oral administration of Ip promoted antioxidant benefits in the myocardium during ischemia and reperfusion, which reduced infarction. We suggest that Mate (a hot drink made from steeped dried leaves of Ip) consumption is a potential cardioprotective habit of indigenous people from southern South American countries, which must be better understood scientifically and ethnographically.